Is a cure for Parkinson's disease hiding inside us?. Issue 8 (August 2022) - Santos, Jaime; Pallarès, Irantzu; Ventura, Salvador
Abstract : α-Synuclein (a-syn) oligomers and fibrils are behind neurodegeneration in Parkinson's disease (PD), but therapeutically targeting them is challenging. Amphipathic and cationic helical peptides inhibit amyloid formation and suppress neurotoxicity by selectively binding the solvent-accessible regions in these toxic species. Can endogenous peptides, like LL-37, constitute a new therapeutic paradigm in PD?